A history of christian thought : from its judaic and hellenistic origins ti existentialism - Tillich, Paul, 1886-1965 (A Touchstone book, 1968)
Lectures delivered in 1953 at Union Theological Seminary, New York, recorded and originally edited by P.H. John.